Perinatal bilateral testicular torsion: A rare emergency with review of literature - Gupta, Amit; Kumar, Akhil; Chandha, Bhavesh; Saroha, Megha (Asian Journal of Medical Sciences, 2014)
Perinatal bilateral testicular torsion is an extremely rare surgical emergency and is subject of debate among surgeons. Urgent surgical exploration and fixation of the other testis are the key points in the management. DOI: http://dx.doi.org/10.3126/ajms.v5i4.9931 Asian Journal of Medical Sciences 2014 Vol.5(4); 103-105